Differential Effects of Low-Frequency TMS of the Motor Cortex on Voluntary and Non-Voluntary Rhythmic Arm Movements - Irina A. Solopova; Victor A. Selionov; Irina Y. Dolinskaya; Germana Cappellini; Yury Ivanenko (Applied Sciences)
Given the cervical spinal cord’s role in locomotor and rhythmic upper limb tasks, its neuromodulation has emerged as an important area of study for understanding human spinal rhythmogenesis. We previously demonstrated that, under unloading conditions, arm muscle vibrostimulation can elicit non-voluntary upper limb oscillations. In this study, we investigated the effects of transcranial magnetic stimulation (TMS) of the motor cortex during both voluntary and non-voluntary (vibration-induced) rhythmic arm movements. We analyzed motor-evoked potentials, mean arm muscle activity, and kinematic parameters of arm movements, including cycle duration and shoulder and elbow joint angular oscillations. Motor-evoked potentials in proximal arm muscles were significantly modulated during both movement types. Notably, low-frequency TMS markedly enhanced non-voluntary arm oscillations, whereas its effect on voluntary movements was statistically non-significant. This differential response is likely due to the absence of characteristic supraspinal influences in sensory-induced spinal activation during non-voluntary movements. These findings align with previous evidence showing that supraspinal pathways facilitate rhythmogenesis in the lower limbs, and they now extend this concept to the upper limbs. Overall, our results suggest that therapies aimed at modulating cervical central pattern generators may benefit from the active engagement of supraspinal motor circuits.